Age and Gender Estimation Using the Osseous Microanatomy: Original Research - Harsh Chansoria; Rolly Chandrakar; H K Chetana; Neelamma Kamadal; Sonal Pamecha; Harveen Kaur; Rahul Tiwari (Wolters Kluwer Medknow Publications, 2024)
Aim: This study was performed with the idea of assessing age and gender utilizing differences in osseous microanatomy in human jawbones. Materials and Methods: The study was conducted retrospectively among human jawbone samples. Various morphometric assessments such as trabecular width, marrow space, and their corelation were studied. In the samples, variations among osteon numbers, differences in the shapes of the osteocytes of jawbones, and amount of inflammation in the bony areas were recorded. Results: It was noted in this study that mean values of the diameter of the Haversian canal and vessel density had a noteworthy increase in female jawbone samples. The amount of osteocytes in both female and male bone samples was also statistically significant in terms of the correlation coefficient. Conclusion: We concluded that more sensitive identification of human remains, that is, age and gender analysis, can be performed by histomorphometric evaluation of bone remains.